IMPLEMENTASI COMPUTATIONAL THINKING PADA ANAK USIA DINI DALAM MELATIH KEMAMPUAN PROBLEM SOLVING - Nuria, Ratri; Rubini (JESA-Jurnal Edukasi Sebelas April, 2026)
The development of 21st-century skills requires early childhood education to emphasize problem-solving abilities through innovative approaches such as computational thinking. This study aims to analyze the implementation of computational thinking in early childhood learning to enhance problem-solving skills. This research employed a qualitative descriptive method through literature review and observation of learning practices. The findings indicate that computational thinking elements—decomposition, pattern recognition, abstraction, and algorithmic thinking—can be effectively integrated into play-based learning activities. Children exposed to these approaches show improved abilities in identifying problems, organizing ideas, and developing structured solutions. The discussion highlights that computational thinking fosters critical and systematic thinking in children when supported by interactive and contextual learning environments. Therefore, integrating computational thinking into early childhood education contributes significantly to developing problem-solving skills in the digital era.